2019
DOI: 10.1097/jhq.0000000000000166
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Approach to Improve Sepsis Outcomes

Abstract: Severe sepsis and septic shock cause significant morbidity and mortality with health care costs approximating $17 billion annually. The Surviving Sepsis Campaign 2012 recommended time-sensitive care bundles to improve outcomes for patients with sepsis. At our community teaching hospital, a review of sepsis management for patients admitted to a medical intensive care unit (ICU) between December 2015 and March 2016 found 70.8% compliance with timing of lactate draw, 65.3% compliance for blood cultures, and 51.4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…An additional study was identified from the review of bibliographies of these previously retained studies for a total of 10 studies included in this systematic review (Figure 1). 12‐21 These 10 studies include 1772 patients with sepsis or septic shock, were conducted during 2006‐2019, and published during the time period of 2008‐2022.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional study was identified from the review of bibliographies of these previously retained studies for a total of 10 studies included in this systematic review (Figure 1). 12‐21 These 10 studies include 1772 patients with sepsis or septic shock, were conducted during 2006‐2019, and published during the time period of 2008‐2022.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacists were specifically identified as key participants in all included studies per the inclusion criteria of the systematic review. Eight studies specifically noted a pharmacist responding to the bedside and interacting with other members of the health care team to consult and facilitate antibiotic order placement and verification, 13‐19,21 one study described pharmacists “huddling” with providers when notified of a sepsis notification, 20 and one study described pharmacists calling the nursing unit if no antibiotics were placed after 15 min of a sepsis alert and facilitating antibiotic ordering if needed, including a protocol which allowed for the pharmacist to select antibiotics if the provider was engaged in other aspects of care 12 . Six studies compared a sepsis bundle response or sepsis quality improvement initiative which included a pharmacist in some capacity, with the comparator group representing prior or concurrent care of sepsis patients without the bundle or quality improvement initiative (eg, historical control) 12‐14,16,17,19 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated a BPA leading to decreased time to antibiotics and other parameters [14][15], nevertheless, it did not lead to an improvement in mortality [14][15]. Personnel driven models, either with a sepsis response team or triage protocol, have also had varying degrees of success with decreasing time to sepsis bundle parameters [7][8][9][10][11], with only one demonstrating a possible mortality benefit [16]. Overall, similar to our study, the vast majority of these interventions have led to some improvement in achieving different sepsis core measurements [7][8][9][10][11][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Achieving the initial sepsis core-bundle within three hours can be challenging, and sepsis may not always be obvious based on the initial presentation. For this reason, a variety of approaches have been developed to maximize adherence to the sepsis core measures [7][8][9][10][11]. One method that could conceivably improve sepsis bundle achievement is having additional staff specifically designed to help with the resuscitation of patients that are critically ill. At our institution, we have developed a novel one-month rotation dedicated to resuscitative care in the ED [12].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the involvement of different professionals in the sepsis alert and severe infection protocols has shown an improvement in the prognosis of these patients beyond the high dependency units. 8,9 Therefore, the inclusion of hospital dermatologists in these multidisciplinary teams could result in better care of patients with severe skin diseases exposed to a higher infectious risk and admitted to dermatology wards (e.g. autoimmune blistering diseases, atopic dermatitis or hidradenitis suppurativa, among others).…”
Section: Editormentioning
confidence: 99%